A communal intervention for military moral injury. (14th April 2022) - Antal, Chris J.; Yeomans, Peter D.; Denton-Borhaug, Kelly; Hutchinson, Scott A.
Abstract: The Moral Injury Group (MIG) at the Corporal Michael J. Crescenz (Philadelphia) VA Medical Center (CMCVAMC) is an example of collaborative care between chaplains and psychologists that engages religious, academic, and not-for-profit communities, as well as the media and other organizations external to the healthcare context. The intervention is primarily informed by a unique conceptualization: the moral injury (MI) of individual veterans is rooted in the unfair distribution of appropriate moral pain and best addressed through communal intervention that facilitates broader moral engagement and responsibility . MI is a public health issue that arises from the unfair distribution of appropriate moral pain and is sourced by the sedimentary layers of structural violence in US institutions related to war, and US war-culture. Preventing veteran suicide and promoting public health requires a larger social analysis and more broad-based, collective and collaborative understanding of, and response to, US war-culture, extending responsibility for MI care and prevention beyond individual veterans in health care institutions and clinical settings to US society.